Cultural heritage as a pedagogical resource in the rehabilitation of people with drug addiction problems - Castillo Gaitán, Bernardo (2022)
Received: 22-09-2021.Approved: 04-11-2021. This article presents an experience in which the Cultural Heritage is a pedagogical resource for the rehabilitation of people with drug addiction problems that takes place in the Rehabilitation Center for Drug Addicts called Rostro de Jesús and illustrates the educational-creative process carried out by the interns for the commemoration of 200 years of independent life.